2021
DOI: 10.1177/1747954120984879
|View full text |Cite
|
Sign up to set email alerts
|

Coaches’ internal model of the tennis serve technique: Knowing or understanding?

Abstract: The understanding of coaches’ knowledge plays a critical role in coach development. This study aimed to examine the internal models of expert and novice tennis coaches and to identify the key distinguishing characteristics between levels. Data was captured by in-depth interviews and analysed using a combination of qualitative and quantitative methodologies. The results revealed that the internal model consisted of seven components including the “functionality” component that has not been reported previously. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 85 publications
(138 reference statements)
1
4
0
Order By: Relevance
“…While coaches didn't believe that there was an ideal bowling technique, they did appear to have a clear idea of what they thought made up a 'good' bowling technique (see Figure 1a). This is in line with findings from tennis (Fetisova et al 2021), sprinting (Waters et al 2020;Thomson, Bezodis & Jones, 2009), golf (Smith et al 2012;Smith et al 2015), ice hockey (Mell et al 2017) gymnastics (Cote et al 1984) swimming (Moreno et al 2006) volleyball (Bian, 2003) and climbing (Mitchell et al 2020). In these studies, expert coaches had clear internal models of the relevant sports technique, which was made up of the key kinematic variables identified in the respective sport-related biomechanical literature.…”
Section: Internal Model Of a 'Good' Fast-bowling Techniquesupporting
confidence: 78%
See 3 more Smart Citations
“…While coaches didn't believe that there was an ideal bowling technique, they did appear to have a clear idea of what they thought made up a 'good' bowling technique (see Figure 1a). This is in line with findings from tennis (Fetisova et al 2021), sprinting (Waters et al 2020;Thomson, Bezodis & Jones, 2009), golf (Smith et al 2012;Smith et al 2015), ice hockey (Mell et al 2017) gymnastics (Cote et al 1984) swimming (Moreno et al 2006) volleyball (Bian, 2003) and climbing (Mitchell et al 2020). In these studies, expert coaches had clear internal models of the relevant sports technique, which was made up of the key kinematic variables identified in the respective sport-related biomechanical literature.…”
Section: Internal Model Of a 'Good' Fast-bowling Techniquesupporting
confidence: 78%
“…Several studies (e.g., Fortiza et al 2021; Smith et al 2015) have demonstrated that coaches are able to identify the key kinematic elements of a sports technique. Fetisova et al (2021) noted that while novice and expert coaches were able to identify the key kinematic elements of a technique, the expert coaches were noticeably different in their ability to chunk these elements into an understanding of the whole technique and had better understanding of the kinetic elements that this combination produces. The coaches in this study demonstrated similarly strong understanding of the kinematic elements of the technique and were able to chunk them together, particularly within the delivery stride.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These limitations also compromise the capacity for sports coaching researchers to utilise established research approaches such as the expert-novice paradigm 7 and limit the widespread application of empirical evidence to the practice of sports coaching expertise because of reduced confidence in research findings based on the inconsistent and questionable methods used to determine expertise. 2 Consequently, the development of a method for measuring sports coaching expertise would be advantageous for enhancing the empirical rigour within this field of research (see [8][9][10] for examples of the various methods used to measure sports coaching expertise in the current literature).…”
mentioning
confidence: 99%